2022
DOI: 10.1049/smc2.12040
|View full text |Cite
|
Sign up to set email alerts
|

Smart city technologies from the perspective of technology acceptance

Abstract: Most studies in the literature aim to discuss and examine the technologies in smart cities. Much less is known about the dynamics of their acceptance by citizens. Therefore, we conducted a systematic literature review of studies examining the acceptance of smart city technologies (SCTs), focussing particularly on Technology User Acceptance Models (TAM). Using a novel framework of SCTs based on the technology visibility and citizen interaction, we categorise them as individual‐based explicit SCTs, collective‐pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“… Kuberkar & Singhal (2020) identified that the existence of conductive infrastructure was necessary for commuters to use a public transport chatbot within a smart city ( Costales, 2022 ). Different studies and theories discussing infrastructure regarding smart transformation and smart cities are entailed in study by Dirsehan & van Zoonen (2022) . Thus, we propose the following hypothesis:…”
Section: Research Backgroundmentioning
confidence: 99%
“… Kuberkar & Singhal (2020) identified that the existence of conductive infrastructure was necessary for commuters to use a public transport chatbot within a smart city ( Costales, 2022 ). Different studies and theories discussing infrastructure regarding smart transformation and smart cities are entailed in study by Dirsehan & van Zoonen (2022) . Thus, we propose the following hypothesis:…”
Section: Research Backgroundmentioning
confidence: 99%
“…Attitude toward usage, as well as the direct and indirect consequences of PEU and PU, all have an impact on Behavioral Intention. PU and PEU are identified as key determinants of citizen adoption of smart city technology in the majority of studies on this topic utilizing the TAM model [64].…”
Section: Technology Acceptance Model Applied To Smart Citiesmentioning
confidence: 99%
“…Indonesia and India were the nations where the most studies were conducted [64]. The few studies that have been conducted in Europe have been in Oslo and Tallinn [77], a case study combining Berlin, Dublin, London, Milan, and Madrid [76], and Luxembourg [75].…”
Section: Technology Acceptance Model Applied To Smart Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Now in some new urban areas in China, more comprehensive pipe galleries are built to realise centralised and convenient management of various underground pipelines. One important goal for the comprehensive management and control of urban underground pipelines network is to realise the scientific planning, meticulous management, and comprehensive information sharing of urban underground pipelines network [1–15].…”
Section: Introductionmentioning
confidence: 99%